Variation in absolute growth rates in Sirohi goats under field condition - SHARMA, M C; PATHODIYA, O P; MISHRA, S; GURJAR, M L (The Indian Journal of Animal Sciences, 2011)
Variations in absolute growth rates in Sirohi goats under field condition were studied. Results revealed that in kids of 0-3 months of age, maximum growth occurred, hence they should be given full care during this period. Management condition should be improved to gain profit from goat rearing.Â